Process Analysis of Producing Single Mesh Warp Knit Fabric Using a Double Needle Raschel Warp Knitting Machine - Permana, Muhammad Indra; Hanif, Ilham Atsir; Hernawati, Resty Mayseptheny (Universitas Insan Cendekia Mandiri, 2025)
This study was conducted to evaluate the flexibility of the double needle bar Raschel machine in producing a mesh fabric design that is conventionally manufactured using a single needle bar Tricot machine. The research involved adjusting several parameters on the Raschel machine, including the number of needle bar positions, guide bar spacing, gudie bar shogging, and run-in values, in order to produce mesh fabric comparable to that produced by the Tricot machine. Subsequently, the physical properties of the resulting fabric were evaluated and compared to those of mesh fabric produced by the single needle bar Tricot machine, using ASTM standards. The test results indicate that the mesh fabric prduced using the double needle bar Raschel machine exhibit similar physical properties—including fabric weight (GSM), course per inch (CPI), wale per inch (WPI), thickness, tensile strength, tear strength, abrasion resistance, and bursting strength—to those of the fabric produced by the Tricot machine. These findings were supported by T-test results, which showed no statistically significant differences (p < 0.05) across all measured properties. The findings indicate that modern double-needle Raschel machines are capable of adapting to replicate the output of older single-needle Tricot maschines, offering a viable solution for production continuity when legacy equipment is no longer operational.